The public health system and the place of autism - Vanini Mandaj; Marcia Simões-Zenari; Daniela Regina Molini-Avejonas (Revista CEFAC, 2023)
ABSTRACT Purpose: to characterize the population with autism spectrum disorder and the Psychosocial Care Network. Methods: a study conducted with patients presented with autism spectrum disorder up to 18 years old treated at the health network in Taboão da Serra, Brazil. Participants’ data were collected from medical records of the Psychosocial Care Network for Children of that city, authorized by the Municipal Department of Health, and quantitatively analyzed. Results: altogether, there were 237 patients with autism spectrum disorder in the said health network by April 2019. Of these, 188 were treated at the Psychosocial Care Network for Children, 110 of them with weekly therapy. There was a predominance of males (73.63%), age range from 3 to 10 years, with a higher percentage of 5-year old (17.27%) patients, and a mean treatment time of 32 months. The youngest age was 2 years old. Half the sample (50%) had weekly therapy and received homeopathic medication; 24 users (21.81%) were referred by speech-language-hearing therapists and 19 (17.27%), by the school they attended. Final Considerations: although the Psychosocial Care Network for Children is the reference in the region, it is known that this facility alone cannot meet all needs of individuals with autism spectrum disorder. A service network coordinated according to patient’s individual needs and the region's reality would ensure their expected rights, decrease public spending, and enable these users to occupy not only one but many places in society.